Peer Mentoring for Staff Development in a Changing Work Environment - Debra Cureton; Patricia Green; Lib Meakin (International Journal of Evidence Based Coaching and Mentoring, 2010)
This paper details the impact of a formalised staff mentoring scheme on people working in a University in the United Kingdom. It considers aspects of a changing political agenda on the working lives of employees and considers how mentoring can mediate its negative effects. Evaluation data indicates that the scheme provides developmental opportunities, contact with others, emotional support and the opportunity for reflection. It is suggested that these findings are transferable to other large, changing, organisational environments where a variety of occupational groups are employed.